2020
DOI: 10.1021/acsami.0c00881
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Photoelectrochemical Synthesis of Ammonia Using Plasmon-Enhanced Black Silicon under Ambient Conditions

Abstract: Although photoelectrochemical synthesis of NH 3 is considered as an ecofriendly and sustainable process under ambient conditions, stable and highly efficient catalysts for the N 2 reduction reaction are still lacking because of the chemically inert nature of the triple bonds in elemental nitrogen and the competitive reaction of water reduction. In this paper, a photoelectrochemical N 2 reduction reaction route is proposed through combining black silicon and Ag nanoparticles using a simple deposition method. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 56 publications
2
35
0
Order By: Relevance
“…h) Comparison chart of FE with existing PEC NRR catalytic systems with present Au/PCN/ n + np + ‐ Si photocathode. [ 18,19,57,58 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…h) Comparison chart of FE with existing PEC NRR catalytic systems with present Au/PCN/ n + np + ‐ Si photocathode. [ 18,19,57,58 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 ] A few studies have recently been reported on PEC N 2 to NH 3 synthesis. [ 18,19 ] Ali et al. have demonstrated PEC NRR using Au nanoparticle‐decorated black Si photoelectrode and obtained an NH 3 production yield of 13.3 mg h –1 m –2 .…”
Section: Introductionmentioning
confidence: 99%
“…The SiIP wafers act as a substrate to be electrodeposited metal Co, and the materials were sulfurated using CVD to finish the fabrication of photocathodes. The optimized photocathodes had a well onset potential of 0.22 V, and the photocurrent density is 10.4 mA cm −2 at −0.45 V. In 2020, B. Wang et al [80] fabricated a plasmon-enhanced black silicon material to synthetic ammonia using photo-electrocatalysis. Through putting silicon into AgNO 3 and HF solution, the Ag nanoparticles and surface nanostructure of black silicon were formed, due to the catalysis of Ag + and the etching of HF.…”
Section: Photocatalysis and Photo-electrocatalysismentioning
confidence: 99%
“…The most commonly used experimental configuration for plasmon-enhanced NRR is a photocatalytic system in which the catalyst is either dispersed in a N 2 -saturated solution or deposited onto a substrate which is then immersed in the reaction solution. In a less frequently used experimental configuration for plasmon-enhanced NRR, an external bias can be applied to drive the reaction along with illumination (photoelectrochemical system); [42,43] however, this will not be covered in this review.…”
Section: Plasmonic Nanomaterials For Nrrmentioning
confidence: 99%